Listeners' participation in radio programs, a radio genre? - Herrera Damas, Susana (2022)
The notable popularity which listeners' participation in radio programs has acquired in the last few years has taken some authors to come to consider it as a radiophonic genre. Nevertheless, a more detailed reading of gene as a pragmatic element makes one discard this consideration and speak more in terms of genres of participation. Currently, these are: the audience's contest, consulting, and interrogatory. The reasons which dissuade one from speaking of participation as a genre are described in the present article and the features which characterize genres are mentioned.